Teachers’ Questioning Strategies to Promote Students’ Critical Thinking in EFL Classroom: Perceptions And Practices - Novitaningrum, Angella; Lestari, Lies Amin; Anam, Syafiâ€™ul (Universitas Malikussaleh, 2020)
This study was intended to describe teachers’ perceptions and practices of questioning strategies to promote students’ critical thinking in EFL classroom. It was a descriptive qualitative research that investigated two English teachers who taught at eighth grade of Junior High School in Trenggalek. Interview and observation were conducted to collect data in order to answer research questions. The findings showed that; first, two teachers who became participants of this study had positive perceptions that practicing appropriate questioning strategies could stimulate students to think critically in learning process, and second, the teachers applied some types of questioning strategies, those were, wait-time, probing, prompting, and reinforcement. In conclusion, reffering to the issue of promoting students’ critical thinking as a result of recent curriculum (K-13), teacher’s questioning strategies was useful to be considered in teaching and learning process, and teachers’ perceptions was one of factors that influence their’ practices in classroom context.